Water under the sand - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
As incredible as it might seem just below the sand dunes of Mauritania (at a depth of only 50-150cm) there is natural moisture. A research worker at the the Institut des Regions Arides de Tunisie (Institute for the arid regions of Tunisia) has...